Analisis Dampak Penerapan Aturan 5 Hari Sekolah Terhadap Motivasi Belajar Siswa Di SMAN 4 Kota Kediri - Rizka Fikri Nabilah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research was motivated by Ministerial Regulation Number 23 of 2017 concerning five school days a week which has been implemented since the 2017/2018 academic year. This regulation aims to improve the quality of education through additional days of effective learning. The focus of this research is the implementation of the five school day rule at SMAN 4 Kediri City and its impact on student learning motivation. This research uses a descriptive qualitative approach with data collection methods through interviews, observation and documentation. The research results show that the five-day school rule is implemented from Monday to Friday, from 07.00 to 15.00 WIB. Saturdays are used for rest or extracurricular activities. Most students are happy because they have more time to rest and develop their non-academic potential at the weekend. However, some students feel tired with busy schedules, especially during the day, which reduces their enthusiasm and motivation for learning. Overall, the implementation of the five school day rule at SMAN 4 Kediri City has both positive and negative impacts on student learning motivation.